Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4028/www.scientific.net/amr.845.462
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbon Concentrations in Reducing Co and Cr Ions Release in Cobalt Based Implant: A Preliminary Report

Abstract: The releases of harmful ions from cobalt based alloy to host tissues have raised significant health concerns. Carbon contents in this alloy may influence ions release but has yet investigated. It is hypothesized that carbon contents in this alloy will help the formation of oxide layer during thermal oxidation process and hence reducing the release of Co/Cr ions after implantation. In this study, Co-Cr-Mo alloy with carbon concentrations of 0.03% and 0.24% were oxidized at 1050°C for 3 hours under atmospheric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Besides that, other different studies done by Mas Ayu et al observed reducing of toxic ions for high carbon content compare to low carbon content under circulation immersion test in simulated body fluid using similar thermal oxidation process [15,16]. Therefore, it can be concluded that carbon content plays an important role when considering the wear tests, corrosion rate and releases of toxic ions in Co-Cr-Mo alloys.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Besides that, other different studies done by Mas Ayu et al observed reducing of toxic ions for high carbon content compare to low carbon content under circulation immersion test in simulated body fluid using similar thermal oxidation process [15,16]. Therefore, it can be concluded that carbon content plays an important role when considering the wear tests, corrosion rate and releases of toxic ions in Co-Cr-Mo alloys.…”
Section: Introductionmentioning
confidence: 84%
“…The surface roughness of all substrate was measured using Mitutoyo SJ-301 surface profilometer while the average roughness of ground samples obtained was 0.1±0.02 µm. Ground samples were left to dry for overnight in the oven at 50ºC before they were taken for next process [15]. Thermal Oxidation Process.…”
Section: Methodsmentioning
confidence: 99%
“…The biocompatible is one of the most fundamental requirements for choosing a metallic implant that is, involving the acceptance of an artificial implant by the surrounding tissues and biological system [1]. Currently, the metallic materials have approved and commonly used in structural implants include stainless steel, cobalt-chromium (CoCr) alloys and titanium (Ti) alloys (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Common surface modification techniques include Chemical Vapor Deposition (CVD) [10], Physical Vapor Deposition (PVD) [11][12][13][14], Ion Implantation [15], Plasma Spray coating [16], Sol Gel [17,18], Nitriding [19], and Thermal Oxidation [20,21]. Among these, the PVD technique shows promising results by offering a low processing temperature (<500 • C) over a wide range of coating thicknesses as compared to other methods.…”
Section: Introductionmentioning
confidence: 99%